ID1 As a Prognostic Biomarker and Promising Drug Target Plays a Pivotal Role in Deterioration of Clear Cell Renal Cell Carcinoma. (30th October 2020) - Qiu, Xiangmin; Gu, Yuping; Ni, Yilu; Li, Qianyin
Abstract : Clear cell renal cell carcinoma (ccRCC) is one of the most common cancers in the world. Our aim is to identify prognostic biomarkers that contribute to the progression of early stage ccRCC and clarify the mechanism. Here, the mRNA microarray expression profile of ccRCC samples was obtained from Gene Expression Omnibus (GEO) (GSE68417). 62 differentially expressed genes (DEGs) were gained by R Studio, including 31 upregulated genes and 31 downregulated genes. Pathway enrichment analysis was performed in DAVID database. Then, the protein-protein interaction network was obtained through STRING database and visualized by Cytoscape. Subsequently, among the network, only inhibitor of DNA Binding 1 (ID1) was significant between low-grade and high-grade ccRCC patients in TCGA data set. After analysis of the corresponding clinical information in R Studio, it is shown that low ID1 expression correlated with poor survival, high probability of tumor metastasis, and relatively high serum calcium. Later, functional enrichment of ID1 in GeneMANIA uncovered that regulating DNA binding is a main characteristic of ID1 in ccRCC, which was validated by Kaplan-Meier curve of ID1 associated genes using KM plotter database and R Studio. Immune infiltration analysis performed by Tumor Immune Estimation Resource (TIMER) revealed that CD8+ T cells and macrophages were prognostic factors. Furthermore, Valproic acid was analyzed to be the most convinced target drug of ID1 identified by Comparative Toxicogenomics Database (CTD). Taken together, ID1, a biomarker of clinical outcome in early stage ccRCC patients, has the potential function of preventing deterioration in ccRCC progression and metastasis.